Impelementasi Strategi Digital Marketing Dalam Menunjang Perluasan Pasar Pada Tenant Ibti Maleo Techno - Dasriana Dasriana; Syamsul Bachri; Zakiyah Zahara; Fera Fera (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
The development of internet technology has initiated the era of industrial revolution 4.0 in the current digital era, where easy and fast access to information has changed the marketing paradigm. The aim of this research is to find out how effective digital marketing strategies are for tenants to reach new markets, the challenges they face when implementing them, how tenants understand the behavior and preferences of target markets in a digital context, and evaluate how effective digital marketing strategies are. In addition, the role of content and platforms in expanding the market will be discussed. This research method is descriptive qualitative, data collected through structured interviews and direct observation with tenants. The research results show that content that is innovative, informative and relevant to the target audience is very important for the success of a tenant's digital marketing strategy. Additionally, it is very important to understand the behavior and preferences of the target market. Tenant measures the success of their strategy by looking at web traffic, revenue, leads, and customer engagement. Primary focus is given to creating high-quality content and developing effective marketing strategies by understanding customer behavior and using appropriate technology. Digital content marketing strategies have proven effective in increasing tenant brand visibility in new markets. This research provides deeper insight into the digital marketing strategies used by tenants, as well as how these strategies can be adapted to the needs and preferences of the target audience to achieve marketing goals.